A Comparison of Polyol Ester and Mineral Oil under Thermal Aging - Rajab, Abdul; Kamil, Insannul; Kamarol Mohd Jamil, Mohamad; Kurniawan, Septian Ari; Rohadi, Nanang; Emiliano, Emiliano (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
Insulating oil was historically dominated by mineral oil due to its cost-effectiveness and good properties. However, the limitations of mineral oil, particularly its availability and environmental concerns, present significant long-term operational risks. Polyol esters, synthesized through specific chemical processes, demonstrate biodegradability and operational safety. This research evaluates the electrical, physical, and chemical properties of both oil types, focusing on parameters such as breakdown voltage, water content, acidity, viscosity, and density. Results indicate that polyol ester oils exhibit a more stable breakdown voltage and better moisture management due to higher water absorption capacity, and greater density stability and viscosity even after prolonged thermal aging. Despite a more pronounced increase in acidity, polyol ester oils positioning as a promising and sustainable alternative for long-term use in oil-filled electrical equipment such as transformers. This aligns with industry objectives for enhanced environmental sustainability and operational reliability.